Return to Work in Post-Revascularization Patients with Acute Coronary Syndrome Undergoing Phase II Cardiac Rehabilitation - Tambunan, Tresia Fransiska Ulianna; Wulandari, Najwa; Kurnain, Dave Nicander; Sianipar, Helisa Rachel Patricie (eJournal Kedokteran Indonesia, 2025)
Returning to work is an essential indicator of functional and psychosocial recovery in post-revascularization patients with acute coronary syndrome (ACS). Participation in Phase II cardiac rehabilitation (CR) is believed to facilitate this process through structured exercise, education, and psychological support. This study aimed to evaluate the effect of Phase II CR on return-to-work outcomes among post-revascularization ACS patients. An evidence-based case report was conducted through a systematic search of PubMed, Scopus, ProQuest, ScienceDirect, and SpringerLink databases from 2013 to 2023. Eligible studies included randomized controlled trials, cohort studies, and systematic reviews that assessed return-to-work outcomes in patients undergoing coronary artery bypass grafting or percutaneous coronary intervention who participated in Phase II CR. Articles not available in full text, published before 2013, or unrelated to return-to-work outcomes were excluded. Three studies met the inclusion criteria: two systematic reviews and one prospective cohort study encompassing approximately 68,000 patients. All reported that CR participation improved physical function, quality of life, and the likelihood of returning to work. The average time to return ranged from 9 to 32 weeks, with higher rates among younger males with white-collar occupations and preserved ejection fraction. Phase II CR significantly enhances recovery and expedites return to work, underscoring its essential role in post-ACS care.